Enhancing the effectiveness of anti-bullying policies through counselling management and collaborative leadership: A structural model in elementary schools of Magelang Regency - Musrifah Musrifah; Didi Supriadi; Welius Purbonuswanto (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
School bullying significantly undermines children's psychological well-being, academic achievement, and school safety in Indonesian primary education. Although proactive school counseling and collaborative leadership are recognized individually in bullying prevention research, their integrated structural relationships remain understudied. This study uniquely examines how these constructs jointly relate to anti-bullying policy effectiveness, addressing Indonesia's Permendikbudristek Number 46 of 2023. Purpose of this study is to examine the associations between proactive counseling management, collaborative school leadership, and anti-bullying policy effectiveness, with school climate as a mediating pathway. Method: Quantitative explanatory survey employing Structural Equation Modeling (SEM-PLS). Sample and Data Collection: 100 respondents (elementary teachers, school counselors, school principals) from elementary schools in Magelang Regency, obtained through purposive sampling. Data collected via standardized Likert-scale questionnaires. Results: Proactive counseling management (comprising systematic counseling services, prevention-based counseling, and teacher-counselor engagement; all loadings >0.79) was associated with anti-bullying policy effectiveness (direct effect = 0.369, p < 0.001). Collaborative school leadership (joint decision-making, counselor support, open communication; loadings ≥0.806) showed stronger associations (direct effect = 0.590, p < 0.001). Both constructs jointly related to policy effectiveness through direct pathways and school climate mediation, explaining 72% of variance (R² = 0.72). Implications: School leaders should establish formalized collaborative decision-making forums and transparent communication systems. School counselors should document services systematically and demonstrate evidence-based program impacts. System administrators should develop integrated professional development combining leadership and counseling competencies, with accountability measures recognizing both contributions.